Smad4 and γ-secretase knock-down effect on osteogenic differentiation mediated via Runx2 in canine mesenchymal stem cells. (July 2022) - Shabir, Uffaq; Bhat, Irfan Ahmad; Pir, Bilal Ahmad; Bharti, Mukesh Kumar; Pandey, Sriti; Gutulla, Sai Kumar; Sarkar, Mihir; Thirupathi, Yasotha; Chandra, Vikash; Sonewane, Arvind; Gutulla, Taru Sharma
Abstract: Cell lineage determination during mesenchymal stem cell (MSCs) differentiation is a highly orchestrated process involving diverse signaling pathways and distinct classes of regulatory molecules. Bone morphogenetic protein (BMP) signaling positively influence the osteoblast lineage determination, whereas the Notch signaling may have a dimorphic action. Effective regenerative therapy for repairing bone defects requires ample knowledge of the signaling pathways responsible for the differentiation of MSCs. To elucidate the signaling pathways that drives canine bone-marrow derived MSCs towards osteogenic lineage, the current work was focused on BMP and Notch signaling. Target genes of Runx2, Smad4 and γ-secretase were silenced by short hairpin RNA (shRNA) in canine MSCs. Evaluation of the effect of gene silencing on in-vitro osteogenic differentiation potential was done by quantitative polymerase chain reaction (qPCR) for osteoblastic markers (Osteocalcin and Osteopontin) and Alizarin red S staining for the extracellular deposition of calcium. Silencing of Runx2 significantly reduced the osteocalcin and osteopontin gene expression while a similar trend was observed in the case of smad 4 silencing and their combination groups, but there was no difference found in Hey 1 expression. Runx2 and Smad4 silencing groups showed very less positive staining with Alizarin red S staining, whereas knockdown of γ-secretase and its combination groups showed reverse results as that of Runx2 and Smad4. Runx2 plays an indispensable part in directing the canine mesenchymal stem cells towards osteogenic lineage. Also, Smad-mediated BMP signaling induced the osteoblast-specific gene expression, whereas the notch pathway negatively regulated the osteogenic differentiation of canine MSCs. Graphical abstract: Unlabelled Image Highlights: Smad4 induces osteogenic differentiation of canine mesenchymal stem cells. γ-secretase inhibits Runx2 mediated osteogenic differentiation in canine mesenchymal stem cells. Knock down studies confirmed the indispensable role of Runx2 in osteogenic differentiation of canine mesenchymal stem cells.